TARI JAIPONGAN GAYANA KARYA GONDO DI KLINIK TARI GONDO ART PRODUCTION - Andini, Gustari Tri; Nuriawati, Risa (Jurnal Seni Makalangan, 2023)
Agus Gandamanah (Gondo) adalah seorang kreator muda Jaipongan sekaligus pemilik sanggar Klinik Tari Gondo Art Production (GAP). Ia banyak menciptakan tari Jaipongan dengan gayanya sendiri. Salah satu karya uniknya adalah Tari Jaipongan Gayana. Nama tarinya dipandang, terdiri atas suku kata ‘gaya’ dan ‘na’ yang memiliki arti ‘gayanya’ Gondo. Gerak-geraknya tidak hanya khas Jaipongan, tetapi memiliki gerak-gerak esensi robotik dan etnik kreatif. Hal inilah yang menarik bagi penulis untuk melakukan pengkajian (penelitian), khususnya kreativitas Gondo dalam penciptaan Tari Jaipongan Gayana. Untuk mengkaji kreativitas Gondo tersebut, digunakan konsep pemikiran Rhodes 4P yaitu: person, process, press, dan product. Penelitian kualitatif dipakai dengan menggunakan dengan pendekatan deskripsi analisis. Adapun hasil yang dicapai yaitu terungkapnya proses kreatif Gondo dalam menciptakan Tari Jaipongan Gayana. Penciptaan tari tersebut, didorong oleh faktor internal dan faktor eksternal, Dilakukan melalui suatu proses yang cukup panjang dan melibatkan seniman lain. Karya tari tersebur dibangun dengan tiga unsur estetika utama yaitu: koreografi, musik, dan rias-busana. ABSTRACT JAIPONGAN GAYANA DANCE BY GONDO AT THE GONDO ART PRODUCTION DANCE CLINIC, June 2023. Agus Gandamanah (Gondo) is a young creator of Jaipongan and the owner of Gondo Art Production (GAP) Dance Clinic. He has created many Jaipongan dances with his own style, one of his unique works is Jaipongan Gayana dance. Some of the unique factors that are interesting among others; Its unique name is taken from the words 'gaya (style)' and 'na' which means Gondo's 'style', and its movements that are not only typical of Jaipongan movements but also having the essence of robotic and creative ethnic movements. This interests the author to do a study (research), especially focusing on Gondo's creativity in creating Jaipongan Gayana dance. In order to achieve optimum results in the study of Gondo's creativity in the creation of the Jaipongan Gayana dance, the author uses the basis of Rhodes' concept of thought (4Ps namely person, process, press, and product). In line with this concept of thought, this qualitative research uses the method of a descriptive analysis approach. The results achieved from this study are the disclosure of Gondo's creative process in the creation of Jaipongan Gayana dance, that is started from himself who is aware of his dancing style which became the conceptual idea in the creation of Jaipongan Gayana dance, which is also supported by internal and external factors, carried out through a quite long process and involved other artists, so that a form of Jaipongan Gayana dance is created which is built with three main aesthetic elements, namely; choreography, musical accompaniment, and make-up and costume. Keywords: Gondo, Creativity, Jaipongan Gayana Dance.